RANCANG BANGUN ALAT UKUR BERAT BADAN OTOMATIS BERBASIS ANDROID - Isagani Zakaria Tarigan; Salomo Sijabat (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2021)
Design and construction of an Android-based automatic weight measurement tool has been carried out. This research was made because of the demands for sophisticated medical support equipment with all the capabilities it has that continues to develop so that effective and efficient medical support equipment can be produced. This tool is designed with the aim of providing information about the measurement data of weight and height to users. Measurement results data will be sent to Android in the form of messages to be stored using the android database system storage.This research method uses qualitative methods, namely: study literature and literature and conduct experiments on the circuit design made, then test the function of the tool with a scale to determine the accuracy of the work of this tool. This tool is made by utilizing the Load Cell sensor as conversion then will sent via GSM SIM 800L, and the data is displayed via the application and SMS on the patient's Android.The test results show that the weight obtained is the result of the load cell sensor measurement. seen the percentage error value for each measurement, which allows the sensor to read errors and possible interference from the compiler program. As long as the% error does not exceed 3%, the module design and build an automatic weight measuring instrument, can be used properly